A comparative reassessment of regional parliaments in Latin America: Parlasur, Parlandino and Parlatino - Mariano, Karina Pasquariello [UNESP]; Bressan, Regiane Nitsch; Luciano, Bruno Theodoro (Inst Brasileiro Relacoes Int, 2017)
The present article assesses and compares the MERCOSUR Parliament, the Andean Parliament, and the Latin American Parliament as instruments to insert political representation and parliamentarians in their respective integration projects. It is argued that the development of regional parliaments in Latin America, however, has not produced substantial changes in regional decision-making processes, which remain the exclusive domain of intergovernmental or interpresidential exchanges.
Keywords: Regional integration; Latin America; Democracy; MERCOSUR Parliament; Andean Parliament; Latin American Parliament